THE READABILITY IN ENGLISH ZONE TEXTBOOK FOR THE TENTH GRADE STUDENTS OF SMA N 2 BANDAR - Lilis Uli Artha Nababan; Sarah Dion Chiquita Marpaung; Fathia Sahrini Simangunsong (Universitas Islam Sumatera Utara (UISU), 2019)
This study was carried out to find out the readability level of the reading texts in English Zone textbook by using Flesch Reading Ease Formula and Cloze Test at the tenth-grade students of SMA N 2 Bandar. The population of this research was the tenth-grade students of SMA N 2 Bandar. The textbook consists of 181 pages with 29 reading texts in it. The researcher took 5 reading texts from the English textbook entitled English Zone published by Penerbit Erlangga and the tenth-grade students of 30 students as the sample. The method used in this study was descriptive analysis using quantitative data. The instruments of the research were Flesch Reading Ease Formula and Cloze Test. The data were analyzed using Flesch Reading Ease Formula which is focused on the average number of the syllables per words. The result of the analysis by using Flesch Reading Ease Formula is grouped into three levels which are Very Easy, Easy, and Fairly Easy. The average readability score for all texts is 82.6 which implies that the texts are in Fairly Easy Level. The result of the analysis by using Cloze Test, the average readability score of the five texts is 51.20% (Independent Level), the texts are predicted to be of appropriate difficulty. Thus, it could be concluded that the reading texts were in the English Zone textbook were not suitable to be used by the students at the tenth-grade students of SMA N 2 Bandar.